DIGITALIZATION OF LOGISTICS HUBS AS A COMPETITIVE ADVANTAGE - E. R. Schislyaeva (Strategičeskie Rešeniâ i Risk-Menedžment, 2020)
The article reveals the concept of a logistics unit, logistics and digital hubs. It is considering the possibility of combining the Northern Sea and New Silk Way sections into a single system on the territory of the Russian Federation. The authors investigated the ways of digitalization of the logistics block of the NSR – NSW with the subsequent creation of a virtual space for the control and redistribution of trade throughout the Russian Federation. The concept of a digitalized logistics block is considered from the point of view of a potentially beneficial project for Russia to collect statistical data and accelerate international transport by instantly redistributing routes.